2021
DOI: 10.3390/molecules26185668
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Monoacylglycerol Lipase in Pursuit of Therapies for Neurological and Neurodegenerative Diseases

Abstract: Neurological and neurodegenerative diseases are debilitating conditions, and frequently lack an effective treatment. Monoacylglycerol lipase (MAGL) is a key enzyme involved in the metabolism of 2-AG (2-arachidonoylglycerol), a neuroprotective endocannabinoid intimately linked to the generation of pro- and anti-inflammatory molecules. Consequently, synthesizing selective MAGL inhibitors has become a focus point in drug design and development. The purpose of this review was to summarize the diverse synthetic sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 129 publications
(214 reference statements)
0
13
0
Order By: Relevance
“…Since AM9928 inhibited tumor growth in the mammary fat pads (Fig. 4 ) and prevented changes in BBB integrity in vivo , resulting in reduced tumor cell colonization in brain, we conclude that MAGL plays a role in TNBC tumor growth and TNBC transmigration across the BBB, in addition to its roles in neurological and neurodegenerative diseases 25 , 26 . Since metastasis to the brain was reported to be associated with damage to the cranial bone (osteolysis) 1 3 , it is important to investigate whether AM9928 may have bone protective effects in mice bearing the GFP-4T1-BrM5 cells.…”
Section: Discussionmentioning
confidence: 69%
“…Since AM9928 inhibited tumor growth in the mammary fat pads (Fig. 4 ) and prevented changes in BBB integrity in vivo , resulting in reduced tumor cell colonization in brain, we conclude that MAGL plays a role in TNBC tumor growth and TNBC transmigration across the BBB, in addition to its roles in neurological and neurodegenerative diseases 25 , 26 . Since metastasis to the brain was reported to be associated with damage to the cranial bone (osteolysis) 1 3 , it is important to investigate whether AM9928 may have bone protective effects in mice bearing the GFP-4T1-BrM5 cells.…”
Section: Discussionmentioning
confidence: 69%
“…Since AM9928 inhibited tumor growth in the mammary fat pads (Figure 4) and prevented changes in BBB integrity in vivo, resulting in reduced tumor cell colonization in brain, we conclude that MAGL plays a role in TNBC tumor growth and TNBC transmigration across the BBB, in addition to its roles in neurological and neurodegenerative diseases. 51,53 Taken together, we suggest that targeting MAGL may provide a new approach to reducing expression of proinflammatory factors as well as inhibiting tumor growth and tumor cell colonization in brain.…”
Section: Discussionmentioning
confidence: 86%
“…24 Recently, 2-AG was shown to be the source for arachidonic acid, the precursor of prostaglandins and other inflammatory mediators. 45,51,53 Accumulated studies showed that MAGL inhibition impaired cell migration, invasion and tumorigenicity in some types of cancers. 20,[22][23][24] Further, MAGL promoted progression of hepatocellular carcinoma via NF-kB mediated epithelial-mesenchymal transition.…”
mentioning
confidence: 99%
“…The proteins were prepared by adding polar hydrogen atoms, and gasteiger charges before docking were processed in MGL Tools. The AutoDock Vina software was used to perform the docking analysis [25]. The size and dimension of the Grid box was selected using co-crystalized ligand coordinates within the target protein [26].…”
Section: Docking Protocolmentioning
confidence: 99%